Enhancing Science Literacy and Critical Thinking Through Project-Based Chemistry Labs with Natural Materials - Ni Pt. Pande Mirah Surya Dewi; Yogo Dwi Prasetyo; Muhammad Syifa Ulkulbi; Syifa Dhiya Atun Nahri (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
The present study by investigating an alternative approach integrating natural materials to create more contextual and meaningful learning experiences. A quasi-experimental design was employed, with the experimental group engaging in hands-on laboratory projects using natural indicators such as purple cabbage extract, eggshell waste, and vinegar, while the control group received conventional instruction. Independent t-test analysis revealed a significant difference between the groups, with the experimental group outperforming the control group in post-test assessments of scientific literacy and critical thinking. These findings indicate that incorporating environmentally friendly, context-based materials into chemistry education could effectively enhance essential skills. Moreover, the project-based approach encouraged students to apply scientific concepts, think critically, and relate their learning directly to everyday life.